Moringa oleifera leaves: could solvent and extraction method affect phenolic composition and bioactivities?. Issue 10 (2nd November 2021) - Bennour, Naima; Mighri, Hedi; Bouhamda, Talel; Mabrouk, Mahmoud; Apohan, Elif; Yesilada, Ozfer; Küçükbay, Hasan; Akrout, Ahmed
Abstract: This study was carried out to evaluate the effect of extraction methods (direct maceration (DM) and successive maceration (SM)) and solvents (dichloromethane (DCM), ethyl acetate (EAc), butanol (But), and aqueous extraction (Aqu)) on the phenolic composition and biological activities of Moringa oleifera leaves cultivated for the first time in Tunisia. Total polyphenol content (TPC), total flavonoid content (TFC) and LC-MS analysis were performed for all extracts. Antioxidant potential by DPPH, metal chelating, and FRAP assays, antibacterial activity against Staphylococcus aureus (ATCC 29213) and Escherichia coli (ATCC 25922) by the minimum inhibitory concentration method (MIC) and cytotoxic properties against lung cancer cells (A549), were determined. Phenolic compounds and biological activities of M. oleifera leaves depend on the method and the solvent used for the extraction of these bioactive substances. The But extract prepared by SM method exhibited the highest amounts of TPC (103.06 ± 0.5 mg GAE/g DE) and showed the strongest potential antioxidant (CI50 = 0.26 mg/mL on DPPH test), antibacterial (MIC = 250 µg/mL) and cytotoxic activities (GI50 = 69.9 µg/mL). LC-MS analysis showed that 28 phenolic compounds of 33 tested standards were found in M. oleifera leaves. The But extract obtained by SM method exhibited the highest amounts of rutin, quercetin and syringic acid.